Kahoot App as a Digital Evaluation Alternative For Online Learning - Novrianti, Novrianti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The use of paper tests has created problems for evaluation such as demotivation, psychological burden, and lengthy scoring process and analysis of answers. Kahoot is an application that offers digital evaluation. Examining the effectiveness of its use is therefore necessary. This Research and Development (R&D) study adopts the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research instrument consists of test items and questionnaire sheets. The results of the validation of items in the category of â€œappropriate to useâ€ include many revisions and recommendations. The results of the test items obtained as many as 46 questions in the valid category. The results of the practicality test in the â€œadequately practicalâ€ category show a score of 3.80. The effectiveness test results in two test classes were 0.068. The research indicates that this product is usable, but the effectiveness test data obtained show that there is no significant difference between digital evaluations using the Kahoot application. However, the norm reference value differs between the two classes. This means that a visually appealing digital evaluation can increase a studentâ€™s enthusiasm for learningPenggunaan paper test telah memberikan kesan membosankan, beban psikologis, proses skoring yang lama serta analisis jawaban pada soal essay merupakan permasalahan evaluasi. Pleh sebab itu, pengembangan evaluasi digital dengan menggunakan Kahoot dan melihat keefektifan pengembangan kedalam penggunaannya sangat dibutuhkan. Penelitian pengembangan ini dengan mengadobsi model ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Instrumen penelitian meliputi butir tes dan lembaran angket. Analisis data yaitu data kuantitatif dan kualitatif. Hasil data kualitatif dari validator tentang butir soal serta produk berisi saran dan masukan. Hasil validasi butir soal kategori layak digunakan dengan banyak revisi, hasil uji coba butir soal diperoleh sebanyak 46 soal dalam kategori valid. Hasil uji kepraktisan kategori cukup praktis dengan skor 3.80. Hasil uji efektifitas pada 2 kelas ujicoba, didapat sebesar 0,068. Berdasarkan hasil pengembangan, maka produk ini terkategori layak untuk digunakan, namun dari hasil uji efektifitas didapat data bahwa tidak ada perbedaan yang signifikan antara evaluasi digital menggunakan aplikasi Kahoot. Hal ini memberikan makna bahwa evaluasi digital yang menarik mampu merubah semangat belajar mahasiswa. Kendala lain juga difaktori oleh kekuatan provider yang digunakan, sehingga kualitas kecepatan dan kepuasan usebilitas tidak terpenuhi.